THE DIRECTOR'S STRATEGY IN BUILDING A THEATER OF MIND ON THE P.O.V. EPISODES OF RADIO FEATURE PROGRAM MINIMAL-IS-ME - Heriyanto Heriyanto; Prasasti Dharma Adi Negoro (Journal of Social Research, 2022)
Background: The production of this radio feature work focuses on providing options for young people to overcome financial problems that have an impact on psychology by applying a lifestyle of minimalism, in addition to the history of minimalism and the direct story of people who apply minimalism in everyday life. minimalism lifestyle is one way to overcome the overconsumption lifestyle that exists in society. Objective: The purpose of creating this production work was to produce a radio feature work with the title "P.O.V." episode of "Minimal-is-me" through the application of Theater of Mind as a director's strategy by maximizing the three elements of radio, namely voice, music and sound effect. Methods: Creation of production works using the methods of stages of creation, pre-production, production, and post-production. Results: The application of fragments in this production can maximize the three elements of radio namely voice, music and sound effects to bring the listener's Theater of Mind to life. so that the listener can feel the characteristics of the radio and can receive the message conveyed well. Conslusion: Feature radio is an excellent program to provide information to listeners because it can be packed with several sub-formats so that the work can be more interesting to listen to. In the Feature program, there are some surprises for the listener because the listener can't guess what will happen next. Featured radio "P.O.V". The episode "Minimal-is-me" discusses the lifestyle of minimalism in society through real cases contained in fragments as well as problem solving through various aspects such as psychology, economics, and how minimalism is beneficial to a person's life